Meeting ultraviolet B radiation requirements of amphibians in captivity: A case study with mountain chicken frogs (Leptodactylus fallax) and general recommendations for pre‐release health screening. Issue 1 (25th September 2014) - Tapley, Benjamin; Rendle, Matthew; Baines, Frances M.; Goetz, Matthias; Bradfield, Kay S.; Rood, David; Lopez, Javier; Garcia, Gerardo; Routh, Andrew
<x xml:space="preserve">Abstract</x> Conservation breeding programmes are a tool used to prevent amphibian extinctions. The husbandry requirements of amphibians are complex. Ongoing research is needed to ensure optimal management of those captive‐bred animals destined, in particular, for reintroduction. The UV‐B and vitamin D3 requirements of amphibians are largely unknown. Metabolic bone disease has been reported in a number of species. These include the Critically Endangered mountain chicken frog (Leptodactylus fallax) reared in captivity on diets supplemented with a high‐calcium multivitamin and mineral supplement containing vitamin D3 but without UV‐B provision. Captive‐bred L. fallax being reared for reintroduction to Montserrat were provided with UV‐B radiation from metamorphosis and were fed on insects supplemented with vitamins and minerals. Overlapping heat, light and UV‐B gradients were provided, mimicking what we believe best represents the natural situation and thereby facilitated self‐regulation of UV‐B exposure. A subset of 10 frogs was periodically radiographed to assess skeletal health. Radiographic bone density and anatomical integrity appeared unremarkable when compared with a wild caught L. fallax. In addition to other routine health‐screening, we recommend that radiography be performed to a structured schedule on a subset of all captive‐bred and reared amphibians to assess skeletal health and to gauge the appropriateness of captive husbandry. We demonstrate here that, through the appropriate provision of a combination of both UV‐B radiation and dietary supplementation, L. fallax can be bred and reared in captivity with healthy skeletal development. Zoo Biol. 34:46–52, 2015. © 2014 Wiley Periodicals Inc.